Historical dialogue and the prevention of mass atrocities - Barkan, Elazar; Goschler, Constantin; Waller, James, 1961- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book brings together a diverse range of international voices from academia, policymaking and civil society to connect historical dialogue with atrocity prevention discourse and provide insight into how conflict histories and historical memory act as dynamic forces, actively facilitating or deterring current and future conflict"--
Historical dialogue and mass atrocities / Elazar Barkan -- Preventing mass atrocities : the role of conflict history in risk, response, and resilience / James E. Waller -- Historical commissions in Germany since the 1990s : potential for social and political conflict solving / Christoph Cornelissen -- Attempted transitional justice and historical dialogue : the case of Israel's Or Commission / Sigall Horovitz -- Historical dialogue in post-conflict Kosovo / Anna De Lellio -- The foundation "remembrance, responsibility and future" and the ambivalence of reconciliation and conflict prevention / Constantin Goschler -- Common history textbooks as a tool of preventing mass atrocities / Karina Korostelina -- Dialogue in the trenches : confronting political narratives in Ugandan secondary schools / Ashley L. Greene -- Is the memory of war in contemporary Europe enhancing historical dialogue / Stefan Berger -- Museums and memorials as sites of dialogue : historical narratives, mass violence, and atrocity prevention / Alexander Karn -- Exhibiting war to understand peace : how do military museums adjust to the need to foster international understanding and peaceful conflict resolution? / Falk Pingel -- Witnessing the past and the present : photography and Guatemala's fight for historical dialogue / Kaitlin Murphy -- "Daisy in the dirt" : visualizing women's historical injustices of war and violence / Olivera Simic -- Memory encroachments and re-plotting the past : cartographies of violence and memory in post-atrocity Argentina, Germany, and the United States / Kerry Whigham.
OCLC-licensed vendor bibliographic record.
Keywords: Atrocities -- Historiography; Genocide -- Historiography; Atrocities -- Prevention; Genocide -- Prevention; Collective memory; Conflict management; POLITICAL SCIENCE / General